Criminal Law Treats for Online Gambling Performers: Investment Fraud Modes - Kamalludin, Iqbal; Suhendar, Heris; Pratami, Bunga Desyana; Yaqin, 'Alamul; Afifah, Nur (Dialogia Iuridica, 2023)
Since 2018 to July 2022, the Ministry of Communication and Information has cut off access to 534,138 gambling content on various digital platforms. This very high number will continue to grow. One of the reasons for the rise of online gambling content is the mode that is used, namely the "bodong" investment mode. Society is promised with unreasonable profits. Blocking efforts are actually one way to prevent and protect the public. Criminal law has regulated gambling in the Criminal Code, as well as if it is done using technology media, it is regulated in the Information and Electronic Transaction Law. This paper examines the regulation of criminal law regarding online gambling in the present, and in the future. This normative law research uses a statutory, comparative, and conceptual approach with prescriptive analysis. The results show that the regulation of gambling in the Criminal Code does not regulate online gambling, the ITE Law still has weak juridical problems in juridical consequences. While in the Draft Criminal Code, it is actually regulated more comprehensively, namely by regulating criminal acts committed with technology in general provisions, but regarding gambling, the Criminal Code concept there are exceptions to permit arrangements taking into account laws that apply in society. Gambling, which has been licensed by the government, has a negative impact on people's lives. The word “without permission” has a meaning that tends to be ambiguous and less relevant.